Quel rôle de la métacognition dans les performances en écriture? Analyse de la situation d’étudiants en sciences humaines et sociales - Escorcia, Dyanne; Fenouillet, Fabien (Canadian Journal of Education/Revue canadienne de l'éducation, 2011)
Our research investigates the relationship between the metacognitive process and the writing performance of students in the first semesters of university. We formulate the hypothesis that the metacognition and the writing performance have a strong and positive relationship. A questionnaire was constructed to measure the metacognition process of students (n= 45). Also, an instrument to evaluate texts was elaborated to measure writing performance. Despite the importance of metaknowledge was emphasized, the data relativizes the relationship between self-regulation and performance. The results are observed according to the evaluation criteria of texts in the context analyzed. Keywords: metacognition, metaknowledge, self-regulation, text, students